2010
DOI: 10.1002/pa.360
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and leadership: Enablers and stumbling blocks

Abstract: Many of the scandals, indiscretions and collapses, over the last few years, at formerly venerated organizations were the results of toxic relationships, dubious economic models, opaque workplace paradigms, as well as questionable collective and individual actions and behaviours of people who, ordinarily, would not be considered ‘typically criminal’. The individuals involved have typically been people with good education, caring parents, were community contributors and, by all accounts, appeared to be upstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…This study provided further support for the moral identity model by Hart and Matsuba ( ) by showing how social influences and the moral orientation affected the moral identity construct of the study subjects of this case study. Because this study focused primarily on moral identity influences relative to education, family, peers, and religion, the results corroborated with research by April et al ( ) that showed how family, education, spirituality, peers, and other influences can enable ethical conduct.…”
Section: Discussionsupporting
confidence: 88%
“…This study provided further support for the moral identity model by Hart and Matsuba ( ) by showing how social influences and the moral orientation affected the moral identity construct of the study subjects of this case study. Because this study focused primarily on moral identity influences relative to education, family, peers, and religion, the results corroborated with research by April et al ( ) that showed how family, education, spirituality, peers, and other influences can enable ethical conduct.…”
Section: Discussionsupporting
confidence: 88%
“…In numerous studies led on administration, the accentuation has been on the initiative procedure, pioneer practices, association with the group of onlookers and authoritative yields. (Yukl, 2002;April et al, 2010;Gardner et al, 2005). Be that as it may, as of late, the initiative has ended up connected with current exploitative practices.…”
Section: Ethical Leadershipmentioning
confidence: 99%
“…Today, the term 'ethics' commonly refers to a written or unwritten ethical system that defines what is culturally considered wrong or right, good or bad (Aronson, 2001) and what kinds of components an ethical and virtuous lifestyle contains (April, Locke and Mlambo, 2010). On the other hand, within the field of leadership, researchers have not yet found a common definition for what constitutes ethics.…”
Section: Ethical Leadershipmentioning
confidence: 99%
“…In many studies conducted on leadership, the emphasis has been on the leadership process, leader behaviors, relationship with audience and organizational outputs (Gardner et al, 2005;April et al, 2010;Aianei, 2006;Powers, 2006;Adeyemi, 2010;Yukl, 2002). However, in recent years, leadership has become associated with current unethical behaviors (see, for example, Enron, WorldCom, Parmalat) in business life, and governments have imposed new regulations enhancing studies in ethical leadership (Brown, Trevino and Harrison, 2005;Resick et al 2011;Den Hartog and Belschak, 2012).…”
Section: Ethical Leadershipmentioning
confidence: 99%
See 1 more Smart Citation